PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN - Putu Cita Ayu; Ni Komang Sumadi (Jurnal Widya Akuntansi dan Keuangan, 2019)
The main purpose of the company is to increase the value of the company. With the achievement of high corporate value, the prosperity for shareholders can increase. Factors that can affect the value of the company is the ownership structure of the company. This study aims to determine the effect of institutional ownership and managerial ownership of corporate value. The value of the company in this study is proportional to the value of Tobin's Q. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) during the period 2014-2016. The method of analysis in this study using multiple linear regression. The results of this study indicate that institutional ownership positively affects the value of the company while managerial ownership does not affect the value of the company.